Mengatasi Hambatan dalam Menyusui untuk Para Ibu - Ningsih, Dewi Andariya; Fitria, Lia; Rahayu, Thira Eva (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Breastfeeding is an effort made by the mother to be able to provide the best nutrition for her baby. It's just that in their practice there are a number of obstacles they face and it's not uncommon for mothers to stop breastfeeding because they can't overcome these obstacles. The purpose of this community service is to understand breastfeeding mothers how to overcome these obstacles and the hope is to provide exclusive breastfeeding. The methods used in the direct approach are surveys, lectures/counseling, discussions and evaluations. The results of this activity breastfeeding mothers can find out how to overcome obstacles in the breastfeeding process and practice it in everyday life